Buffalo (Bubalus bubalis) lymphocytes: Separation and identification using conventional methods and cross-reactive monoclonal antibodies - RAWAT, J; GOEL, M C (The Indian Journal of Animal Sciences, 2013)
Peripheral blood mononuclear cells(MNC) of buffalo were separated by density gradient centrifugation of the buffycoat followed by tris.NH4 CI bufier lysis of erythrocytes(E). This gave a yield of 83.84 % MNCs. By layering of MNCs on plastic surface, a nonÂ·adherent (PÂ·NAC) lymphocyte enriched preparation containing about 10% monocytes was obtained. The P-NAC were utilized for comparing cell surface markers for the identification of B cells, T cells and their subsets. Of the 4 markers used for T lymphocytes, E-rosetting and a naphthyl acetate esterase staining were not satisfactory while labelling with peanut agglutinin (PNA) and cross reactive monoclonal antibody (MAb) BAQ82A (bovine CD6 specific) detected highest mean per cent of 4.66 and 41.72 lymphocytes, respectively. The percentage of PNA- binding cells increased to 72% after T cell enrichment with immunoafiinity panning. The percentage of cells which had receptors for Fcy or were labelled with MAb, CCAT83B (BoT4 specific) in P-NAC , was almost similar and seems to be valid markers for buffalo T helper cells. The BoT8 - specific MAb BAQ111A, however, labelled higher percentage of cells than those having receptors for Fcy: The mean percentage of lymphocytes which had surface immunoglobulins(SIg) or which could fonn rosettes with E coated with Erthrolyte antibody and complement(EAC), was almost similar but less than those labelled with cross- reactive MAb BAQ44A (bovine B lymphocyte specific). The use of nylon wool column for separation of T and B lymphocytes was unsatisfactory but direct panning of monocyte- depleted lymphocytes with,antibuffalo Ig-coated plates served to positively select SIg+ cells.